P296 Pet – mr in paediatric neurology, the early experience. (6th June 2017) - Francis, Peter; Cain, Tim; Tudball, Coral
Abstract : The first paediatric PET-MRI in Australia was installed at the Royal Children's Hospital Melbourne in April 2016, and since then we have performed more than 130 paediatric neurology epilespsy studies. PET-MRI has proven to be very helpful particularly in the evaluation of paediatric epilepsy with planning for epilepsy surgery. Focal cortical dysplasia, sulcal dysplasia and tumours are more accurately planned for surgery. There has been strong and increasing interest from the paediatric neurology community. We present our initial experience and cases illustrating the utility of the PET component of the study in guiding the interpretation of the synchronously obtained MRI.